Sengsara Kristus dalam Implementasinya bagi Upaya Penginjilan - Anna Mariana Poedji Christanti (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2021)
Abstract: The decline of faith in the present, should motivate every Christian to actively preach the gospel. Gospel preachers need to be equipped with the concept of the balance of God’s love and justice. This writing is the result of literature reseach. The focus is on the balance of God’s love and justice, which is expressed in the medical, psychological, and spiritual misery of Christ. The aim is for the development of evangelistic efforts and the firmness of the faith of Christians.